Inequality and class in rural New Zealand - Pomeroy, Ann (New Zealand Sociology, 2022)
A preliminary exploration of an under-researched topic, class divisions in rural New Zealand, points to major inequalities that are highly likely to be affecting the life chances of some rural residents. Census and socio-economic deprivation data for the rural component of 20 of New Zealand’s territorial authorities show there is considerable variation between the three rural settlement types (rural districts or open-countryside outside centres of 300+ people, rural centres of 300-999 people, and minor-urban centres of 1000-10,000 people). The clear inequalities between these settlement types points to class divisions in rural New Zealand. The analysis shows that in addition to social distinctions such as ethnicity and gender, and the impact of geographic location on access to services, class is also likely to be differentially impacting on the life chances and access to services and material possessions of New Zealand’s rural population